2022
DOI: 10.1108/nfs-02-2022-0058
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation and acceptability of cookies produced from wheat (Triticum aestivum) flour substituted with avocado puree as fat substitute

Abstract: Purpose The purpose of this study is to evaluate the quality and sensory properties of cookies produced from wheat flour using avocado puree as fat substitute. Design/methodology/approach Cookies were produced from wheat flour using avocado puree as fat substitute in ratio 0%, 25%, 50%, 75% and 100%, respectively. The formulation of margarine and avocado puree blends was done by using D-Optimal Mixture Design. In all, 20 samples were produced from each substitution level and analyses were done in triplicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Ajatta et al (2016) also reported a high WAC in BF and an increase in WAC with higher BF substitution in various ratios of BFWF composite flours. The WAC is a valuable indication of the ability of flour to associate with water molecules and absorb it during processing (Kraithonget al, 2018;Adeyeye et al 2023;Njoku et al, 2023). High WAC implies improving the food product's texture, viscosity and handling (Umezuruike and Nwabueze, 2017).…”
Section: Farinographical and Extensographical Properties Of The Indiv...mentioning
confidence: 99%
“…Ajatta et al (2016) also reported a high WAC in BF and an increase in WAC with higher BF substitution in various ratios of BFWF composite flours. The WAC is a valuable indication of the ability of flour to associate with water molecules and absorb it during processing (Kraithonget al, 2018;Adeyeye et al 2023;Njoku et al, 2023). High WAC implies improving the food product's texture, viscosity and handling (Umezuruike and Nwabueze, 2017).…”
Section: Farinographical and Extensographical Properties Of The Indiv...mentioning
confidence: 99%